La Havana-Bogota Peace Agreement and the Transitional Justice in Colombia - Erçakıca, Mustafa (Comparative Cultural Studies - European and Latin American Perspectives, 2022)
In this article armed conflict in Colombia and the post-agreement period, which is still very recent, are evaluated. The armed conflict between the armed forces of the State and the FARC-EP has terminated in Colombia by making The La Havana-Bogota Peace Agreement. By the virtue of this agreement, the post-agreement period in Colombia is started. With this agreement, some other various steps have been taken to increase the political participation of the Colombian people and the democratization in Colombia. The Integrated System, containing the Commission for the Clarification of Truth, Coexistence and Non-Repetition, the Unit for the Search of Missing People Due to and in the Context of the Armed Conflict and the Special Jurisdiction for Peace, was established. Colombia is a current issue for international community in the context of transitional justice period.